Induced stability of granular slopes in the presence of interstitial matter - Pastor, Marissa G.
The dynamics of the angle of repose of binary mixtures θmix, as a function of the concentration of the interstitial matter in a granular step setup is reported. As the concentration of interstitial matter is increased, the presence of a maximum angle or repose θmix greater than the θ's of i components is observed. The non-monotonic trend is evident only for mixtures with components having large size (e.g. volume) difference. Three different methods are used to interpret the results: (1) stability increase hypothesis due to increased effective coordination number, (2) an analytical model utilizing Mohr-Coulomb Analysis, and (3) a cellular automata model. All of these paradigms capture the occurrence of a maximum θmix in the experiments. Moreover, the physical properties of the interstitial and granular materials (i.e. particle geometry and surface roughness) is found to play a vital role in the stabilization of binary heaps while variations in the experimental conditions show no significant effects in the dynamics of θmix. The work provides new insights in understanding the natural formations of slopes based on first principles. PACS Numbers: 81.05Rm (Granular materials), 83.10Rs (Computer simulation of molecular and particle dyanamics), 02.70.Ns (Molecular dynamics and particle methods), 45.50.Tn (Collisions), 45.50.Dd (General motion)